Antimycobacterial N-alkoxyphenylhydroxynaphthalenecarboxamides affecting photosystem II - Gonec, Tomas; Kralova, Katarina; Pesko, Matus; Jampilek, Josef (Bioorganic & medicinal chemistry letters, 2017)
N-(Alkoxyphenyl)-2-hydroxynaphthalene-1-carboxamides (series A) and N-(alkoxyphenyl)-1-hydroxynaphthalene-2-carboxamides (series B) affecting photosystem (PS) II inhibited photosynthetic electron transport (PET) in spinach chloroplasts. Their inhibitory activity depended on the compound lipophilicity as well as on the position of the alkoxy substituent. The most potent PET inhibitors were 2-hydroxy-N-phenylnaphthalene-1-carboxamide and N-[3-(but-2-yloxy)phenyl]-2-hydroxynaphthalene-1-carboxamide within series A (IC50=28.9 and 42.5µM, respectively) and 1-hydroxy-N-(3-propoxyphenyl)naphthalene-2-carboxamide and 1-hydroxy-N-(3-ethoxyphenyl)-naphthalene-2-carboxamide (IC50=2.0 and 3.1µM, respectively) within series B. The inhibitory activity of C'(3) or C'(4) alkoxy substituted compounds of series B was considerably higher than that of C'(2) ones within series A. The PET-inhibiting activities of both series were compared with the PET inhibition of isomeric N-alkoxyphenyl-3-hydroxynaphthalene-2-carboxamides (series C) reported recently. Interactions of the studied compounds with chlorophyll a and aromatic amino acids present in pigment-protein complexes mainly in PS II were documented by fluorescence spectroscopy. The section between P680 and plastoquinone QB in the PET chain occurring on the acceptor side of PSII can be suggested as the site of action of the compounds.
Keywords: Hydroxynaphthalenecarboxamides; Hill reaction; Naphthalenes; antibakteriální látky; Photosystem II Protein Complex; Electron Transport; transport elektronů; Anti-Bacterial Agents; Structure–activity relationships; Spinacia oleracea; Plant Proteins; fotosystém II (proteinový komplex); naftaleny; rostlinné proteiny; Photosystem II